Students View on Text Chats (CH), Forum Discussion (FR), and Online Learning Interaction (LI) (Jurnal Teknologi (Sciences & Engineering), 2014)
The objective of this research is to get the students’ opinion on using online forum discussion (FR), text chatting (CH), and online learning interaction (LI). Quantitative and qualitative approaches were used through questionnaires and semi-structured questions which were administered to 133 Social Science students of a Malaysian public university, selected using volunteer random sampling. The result of a descriptive analysis shows that FR was more favoured by the students (mean = 4.11) compared to CH (mean = 3.87) and LI (mean = 4.06). Next, the path analysis found that FR is more significant (r = 0.59, p < .05) compared to CH (r = 0.35, p < .05) towards LI aspect. However, FR and CH are interrelated with critical ratio (C.R) = 6.455, p < .05). Qualitative analysis found that student’s views leaned more towards FR because of its ability to generate meaningful discussions in LI compare to CH according to some of stated reasons. From the perspective of LI, students need a learning environment that encourages them to participate in learning activities actively and involves the lecturer as learning supervisors. The results of analysis explain that the online FR and CH have different perspectives of focus of use. The implication of this study suggests the involvement of students and lecturer during design and development stage of online learning process.